Diffusing useful knowledge: The monitorial system of education in Madras, London and Bengal, 1789 - 1840 - Tschurenev, Jana (Paedagogica historica, 2008)
This paper addresses some fundamental aspects of the circulation of knowledge connected with the spread of the first global model of school management and classroom organisation in the early nineteenth century: the so-called "monitorial system of education" or, as it was named after its "inventors", the "Bell-Lancaster Method". By looking at the communication of educational ideas between England and the early British possessions in India, this paper first analyses the actors involved in this process, especially their agendas and means. Inspired by the widespread belief in the powers of education to improve both society as a whole and individuals, educational activists gathered in a number of committees and organisations - among whom the "British and Foreign School Society" proved most influential. Protestant missionary societies also became active in the field of popular education. The monitorial system of education attracted social reformers, British as well as Indian, and missionaries to whom it appeared to be a technology with civilising powers, a rational instrument to morally uplift and, at the same time, subject individuals "to their respective places" in society. Second, the paper looks at the processes of hybridisation and transformation of the pedagogical knowledge that was communicated between India and England: the origins of the monitorial system in an orphanage school at Madras, its export to London, where it was developed into a standardised model, and its subsequent "re-import" into India. Finally, reports about the implementation of the monitorial system in India again had an impact on English public discourses on education.